On predictive entrepreneurial action in uncertain, ill-structured conditions - David J. Rapp; Michael Olbrich (Review of Managerial Science, 2020)
Decision-making is at the heart of entrepreneurship. Unsurprisingly, entrepreneurship research has engaged with processes of entrepreneurial decision-making resulting, most importantly, in the notions of causation, effectuation, and enactment. Nevertheless, the range of processes delineated to date remains somewhat incomplete. Drawing on crucial insights from the analysis of decision problem structures reveals that entrepreneurship theory has lacked a process that both recognizes the ill-structuredness typically surrounding entrepreneurial decisions and places prognoses center stage. While effectuation implicitly addresses structural defects but denies prognoses a central role, causation emphasizes the importance of predictions while being associated with well-structured, risky environments, and thus, unaffected by structural defects. Theorizing about a combination thereof, that is, a process recognizing and considering the ill-structuredness of entrepreneurial environments yet building on predictions of the future is overdue. This paper, therefore, seeks to foster a more comprehensive yet nuanced understanding of entrepreneurial decision-making processes by outlining the intrinsic features of one such process that we term execution and relating it to existing processes.
Keywords: D81; L26; B50; B06; 650; Causation; Effectuation; Enactment; Uncertainty; Ill-structuredness; Execution